The effects of Tai Chi Chuan training on lower limb inter-joint coordination during stair negotiation in patients with knee osteoarthritis - Zheng, Jiaqi; Hou, Meijing; Wang, Xiangbin (The Journal of the International Society of Chinese Health Practices, 2024)
Aim: Human locomotion is inherently unstable and thus needs a complex postural control system that activates the lower extremity muscles, producing related coordinated movements of the hip, knee, and ankle joints, to maintain the center of gravity within its base of support. Patients with knee osteoarthritis (OA) have changes in the lower limb sensorimotor function, resulting in impaired inter-joint coordination and postural stability, and increasing the risk of falls in daily life. Stair negotiation is a common but difficult and hazardous locomotor task for individuals with knee OA. Compare with walking, it requires greater postural control via highly coordinated joint movements. Studies have shown that individuals with knee OA demonstrated smaller knee flexion angles in conjunction with larger hip flexion angles and smaller ankle dorsiflexion angles during stair ascent. When descending the stair, they were observed to move their center of gravity anteriorly at the initiation of stepping down, accompanied by a decrease in knee angle and hip angle during the early stance phase, but no significant change in the ankle. Tai Chi Chuan (TCC), an ancient Chinese aerobic exercise can improve muscle strength and balance of lower limbs. However, there are few studies on the effects of TCC training on inter-joint coordination of the lower limb in individuals with knee OA. Cyclogram as a method of reflecting inter-joint coordination, have been used to investigate coordination patterns during level walking in individuals with knee OA, but only the hip-knee cyclogram in the sagittal plane was studied. The study aimed to explore the performance of hip-knee, hip-ankle, and knee-ankle coordination in the sagittal plane during stair negotiation after TCC training in individuals with knee OA and to investigate if TCC training is more efficient than balance training for improving inter-joint coordination. Method: 28 participants with knee OA in the TCC group and 24 participants with knee OA in the control group eventually completed the intervention. The TCC group adopted Yang's Ten-form of Tai Chi Chuan training. It consists of commencement, repulsing the monkey, brushing the knee and twisting step, parting the wild horse’s mane, waving hands like clouds, golden cock stands one leg, kicking with heel leading, grasping the peacock's tail, crossing hand and closing. Whereas the control group underwent balance training, which included single-leg standing, walking forward, walking backward, side stepping, and single-leg tapping. The training lasts for 12 weeks and twice a week, 1 hour each time. Participants were evaluated with baseline characteristics, relevant scales (such as WOMAC, Berg, etc.), and three-dimensional gait analysis before and after the intervention. A 1.8-m walkway and a customized eight-step staircase (height: 20cm, tread depth:30 cm) with handrails on both sides were used to mimic daily stair negotiation in a university gait laboratory. At the top of the staircase, a 1-m long and 2.5-m wide platform with a fence around the platform was equipped for security. 75 reflective markers according to the calibrated systems technique protocol were attached to the anatomical landmarks of each subject. The marker trajectories were recorded at a sampling rate of 100 Hz by a 3D motion capture system equipped with ten infrared cameras (Oqus7+, Qualisys AB, Sweden). Participants were asked to ascend the stairs to the top and descend back to the floor at their comfortable speeds. Then, Visual3D (V6, C-motion Inc., Germantown, MD, USA) was used to analyze subjects' kinematic data during stair negotiation. The marker trajectories were filtered using a zero-lag fourth-order low-pass Butterworth filter with a cutoff frequency of 6 Hz, and gait parameters such as gait phase, and range of motion (ROM) on the affected side. After acquiring related gait parameters, the cyclograms in hip-knee, hip-ankle, and knee-ankle using MATLAB were generated by simultaneously plotting the hip, knee, and ankle joint angles in the sagittal plane throughout the entire gait cycle. The cyclograms used in this study were plotted in a clockwise direction from the stance phase to the swing phase, divided by the heel strike point and the toe-off point. Then, we obtained the average value of all cyclograms parameters including perimeters and areas of the stance phase, swing phase, and total gait cycle. A comprehensive analysis of the perimeters, areas, and displayed cyclograms can reflect the coordination of the lower limb joints. Statistically, mixed between-within-subjects ANOVAs were used to analyze the intergroup effect, time effect, and interaction effect. Result: There were no significant differences in age, sex, height, weight, BMI, and K/L grade between the two groups. After 12 weeks of Tai Chi Chuan training and balance training, WOMAC scores were lower and Berg scores were higher than before intervention. Hip-knee, hip-ankle, and knee-ankle cyclograms in the sagittal plane are shown at the end of the body of the abstract. Whether ascending or descending the stair, the ROM of the hip decreased in two groups after the intervention. Compared with pre-intervention, the ROM of the knee and ankle in both groups only decreased during the stair descent. And the ROM of the knee was greater in the TCC group than in the control group. During stair ascent, the swing phase perimeters and total perimeters of hip-knee, hip-ankle and knee-ankle cyclograms in the TCC group and the control group were significantly reduced compared with pre-intervention. The stance phase area of the hip-ankle cyclogram of the TCC group was significantly greater than that of the control group. During stair descent, significant time main effects indicated decreased all perimeter parameters of hip-knee cyclogram, total perimeters of hip-ankle cyclogram, the swing phase perimeters, and total perimeters of knee-ankle cyclograms in both the TCC group and control group after intervention. There were also fewer total areas in the hip-knee and hip-ankle cyclogram in the two groups. In the hip-ankle and knee-ankle cyclograms, the perimeter of the stance phase had significant interaction effects between time and group. The results of simple effect analysis showed that the TCC group decreased after the intervention while it did not change the control group. And the perimeter of the hip-ankle cyclogram in the stance phase was significantly smaller in the Tai Chi group than in the balanced group after the intervention. In addition, the investigation of simple effects analysis of area parameters with significant interaction effects for the stance phase of all cyclograms and the total knee-ankle cyclogram. It shows that only the TCC group had a decrease in cyclograms’ areas after the intervention. Conclusion: Twelve weeks of tai chi training and balance training both improved symptoms and balance function in participants with knee OA. Following the intervention, participants with knee OA during stair ascent from the toes off the ground to the next stair exhibited increased hip flexion, knee flexion, and ankle dorsiflexion angles, were able to transition more quickly to the next heel strike, and therefore demonstrated a tendency for the cyclograms to decrease in perimeters. In addition, the reduction in the ROM of the hip in both groups after the intervention may be due to a change in the compensatory strategy of the patients due to their improved balance as well as muscle strength, which does not require increased foot clearance ability to prevent falls by increasing hip joint angle. The area of the hip-knee cyclogram during the stance phase was significantly larger in the TCC group than in the control group probably because of inherent intergroup differences in the ROM of the knee between the two groups. The cyclograms during the descending stair period observe that the hip flexion angle in patients with knee OA is greater than pre-intervention in both the stance and swing phase, thus affecting the change in cyclograms perimeters and areas. Moreover, the increase in hip flexion angle in the stance phase after the intervention in the TCC group was accompanied by a decrease in knee flexion angle, which led to a decrease in the knee joint load, and therefore a significant decrease in the area in the hip-knee cyclogram in the stance phase. This change is consistent with the concept of “loosening the waist and dropping the hips” and “forcing the hips to strengthen the knees” in TCC training. In addition, the hip-ankle cyclogram and knee-ankle cyclogram in the TCC group showed a reduction in the ankle plantarflexion angle during the stance phase, improving the delay from heel strike to maximum ankle dorsiflexion angle in patients with knee OA. And reduced ROM of the hip, knee, and ankle joints in both groups may indicate improved postural control and a reduced range of center of gravity movement in patients with knee OA, without the need for compensatory increases in joint range of motion to increase stability. In summary, both TCC and balance training improved the inter-joint coordination in the lower limb during stair negotiation in patients with knee OA, and the TCC intervention was more pronounced in improving lower limb coordination during stair descent. In addition, the symptoms and balance function of KOA improved after the intervention, and the perimeters and areas of the cyclograms tended to decrease after the intervention. Therefore, the cyclograms can be used as an objective basis for the subsequent determination of whether the sensorimotor system function of patients with KOA improves or not, as well as an effective method to study movement patterns and inter-joint coordination.